2019
DOI: 10.1029/2018ja026328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low‐Harmonic Magnetosonic Waves on the Radiation Belt Electrons Inside the Plasmasphere

Abstract: In this paper, we presented two observational cases and simulations to indicate the relationship between the formation of butterfly‐like electron pitch angle distributions and the emission of low‐harmonic (LH) fast magnetosonic (MS) waves inside the high‐density plasmasphere. In the wave emission region, the pitch angle of relativistic (>1 MeV) electrons becomes obvious butterfly‐like distributions for both events (near‐equatorially mirroring electrons are transported to lower pitch angles). Unlike relativisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…The electron butterfly pitch angle distribution (PAD), which is defined as the distribution with peak flux off 90° pitch angle, has been a research hotspot in the community of magnetospheric physics during the Van Allen Probes era (e.g., Hua et al, ; Li et al, ; Li et al, ; Li et al, ; Maldonado et al, ; Ni et al, ; Xiao et al, ; Yu et al, ; Zhao, Li, Blake, Fennell, Claudepierre, Baker, Jaynes, & Malaspina, , Zhao, Li, Blake, Fennell, Claudepierre, Baker, Jaynes, Malaspina, & Kanekal, ). The butterfly PAD observed at a certain location can provide clues about what specific physic processes have taken place there, and they may improve the understanding of the dynamics of the radiation belts.…”
Section: Introductionmentioning
confidence: 99%
“…The electron butterfly pitch angle distribution (PAD), which is defined as the distribution with peak flux off 90° pitch angle, has been a research hotspot in the community of magnetospheric physics during the Van Allen Probes era (e.g., Hua et al, ; Li et al, ; Li et al, ; Li et al, ; Maldonado et al, ; Ni et al, ; Xiao et al, ; Yu et al, ; Zhao, Li, Blake, Fennell, Claudepierre, Baker, Jaynes, & Malaspina, , Zhao, Li, Blake, Fennell, Claudepierre, Baker, Jaynes, Malaspina, & Kanekal, ). The butterfly PAD observed at a certain location can provide clues about what specific physic processes have taken place there, and they may improve the understanding of the dynamics of the radiation belts.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies (e.g. Horne et al, ; Yu J et al, ), the tangent of the wave normal angle ( X = tan θ ) is assumed to be a Gaussian distribution alignleftalign-1gx=expXXmXw2,Xmin<X<Xmaxalign-2 with peak at X m = tan 89°, half‐width X w = tan 86°, and lower and upper cutoffs X min = X m − X w and X max = X m + X w . Following previous studies (Lyons, ; Glauert and Horne, ), the bounce‐averaged diffusion coefficients in a dipole field can be written as: alignleftalign-1Dαα=1Tαeq0λmDααcosαcos2αeqcos7λdλ,align-2 alignleftalign-1Dαp=1Tαeq0λmDαpcos4λ1+3cos2λ1/4cosαeqdλ<...>…”
Section: Proton Scattering Ratesmentioning
confidence: 99%
“…According to previous studies (e.g. Horne et al, 2007;Yu J et al, 2019), the tangent of the wave normal angle (X = tan θ) is assumed to be a Gaussian distribution…”
Section: Figures 2c and 2dmentioning
confidence: 99%
“…It is found that when the transit‐time scattering is considered, the interaction range of particle pitch angles and energies could become much broader (see Figure S1 in the supporting information for more detailed description), as compared to the quasilinear resonant theory (Bortnik & Thorne, 2010; Lei et al, 2017). Generally, one uses test particle simulations to investigate this well‐known effect (Li et al, 2014; Yu et al, 2019), and it usually costs a large amount of computation resources to obtain a diffusion coefficient map but gives a poor insight into the dominant physical processes of wave‐particle interactions. Alternatively, Bortnik et al (2015) provided an analytical approximation which can capture the main results of test particle simulations but take a computation time about 4 order of magnitude faster than the latter.…”
Section: Introductionmentioning
confidence: 99%